Evaluation of nonpharmacological nursing practices related to thirst and the thirst of patients in the intensive care unit - Çelik, Sevim; Şengül, Münevver; Karahan, Elif (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Thirst is a significant symptom and stressor among patients in the intensive care unit. The aim of this study is to assess the severity of thirst and associated symptoms experienced by patients in the intensive care unit, and to evaluate the nursing practices related to addressing thirst. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This descriptive and correlational study involved a total of 66 patients in the intensive care unit. Severity of thirst experienced by these patients was assessed using a numeric rating scale. The nursing practices related to assessing thirst severity on admission to the unit, on the third day, and on the seventh day were also recorded. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Our findings showed a statistically significant increase in the levels of thirst, dry mouth, bad taste and odor in the mouth, as well as sensitivity and dryness in the throat among patients on the seventh day of hospitalization (p<0.05). Among nursing interventions, communication with the patient was the most frequently applied intervention during the seven-day period, with a range of 98.5% to 100%, biochemical control (100%), ventilation of the unit (100%), and temperature regulation (100%) were also frequently applied. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The patients had all the symptoms of thirst.The frequency of nursing interventions increased in parallel with the severity of thirst.